How to Deal With Kidney Retransplantation—Second, Third, Fourth, and Beyond. Issue 4 (6th July 2021) - Sageshima, Junichiro; Chandar, Jayanthi; Chen, Linda J.; Shah, Rushi; Al Nuss, Ammar; Vincenzi, Paolo; Morsi, Mahmoud; Figueiro, Jose; Vianna, Rodrigo; Ciancio, Gaetano; Burke, George W.
Abstract : Kidney transplantation is the best health option for patients with end-stage kidney disease. Ideally, a kidney transplant would last for the lifetime of each recipient. However, depending on the age of the recipient and details of the kidney transplant, there may be a need for a second, third, fourth, or even more kidney transplants. In this overview, the outcome of multiple kidney transplants for an individual is presented. Key issues include surgical approach and immunologic concerns. Included in the surgical approach is an analysis of transplant nephrectomy, with indications, timing, and immunologic impact. Allograft thrombosis, whether related to donor or recipient factors merits investigation to prevent it from happening again. Other posttransplant events such as rejection, viral illness (polyomavirus hominis type I), recurrent disease (focal segmental glomerulosclerosis), and posttransplant lymphoproliferative disease may lead to the need for retransplantation. The pediatric recipient is especially likely to need a subsequent kidney transplant. Finally, noncompliance/nonadherence can affect both adults and children. Innovative approaches may reduce the need for retransplantation in the future.